Pertussis Vaccination: The Challenges Ahead - Guiso, Nicole; Koenig, Carl Heinz Wirsing von (Seminars in Respiratory and Critical Care Medicine, 2025)
Pertussis, a highly contagious respiratory disease, is preventable with vaccine. Two types of vaccines are used around the world: whole-cell pertussis vaccines (wP), which contain inactivated bacterial suspensions are difficult to produce and induce some side effects, and acellular pertussis vaccines (aP), which contain one to five purified bacterial antigens, chemically or genetically detoxified. Both the vaccines succeeded in massively decreasing child deaths caused by pertussis. However, irrespective of vaccination, the disease is still endemic around the world, and cycles of pertussis are still observed every 3 to 5 years in both wP- or aP-vaccinated regions. The interval between each cycle, and the intensity and incidence of the disease during these cycles vary. The first challenge ahead is to rapidly increase vaccine coverage by vaccinating infants on time, introducing regular vaccine boosters throughout life, and vaccinating pregnant women. The second challenge is to introduce an effective disease surveillance such as a pediatric hospital surveillance, allowing an estimation of the incidence of severe disease in the pediatric population, and/or a sentinel surveillance, allowing to detect changes in the incidence of the disease in the population. All surveillance systems require a functional network of physicians in the country aware of the clinical forms of the disease in children, adolescents, adults, and seniors. Surveillance is required to adapt vaccine strategies according to the vaccine type and to follow the evolution of the agents of the disease. The third challenge is to pursue research to improve these vaccines. However, before changing vaccines once again, an evaluation of the exact consequences of aP or wP vaccines under specific vaccine strategies needs to be carefully carried out.
Keywords: pertussis; vaccines; vaccine strategy